Cerebral palsy in preterm infants - Demeši Drljan, Čila; Mikov, Aleksandra; FilipoviĆ, Karmela; TomaŠeviĆ TodoroviĆ, SneŽana; KneŽeviĆ, Aleksandar; Krasnik, Rastislava (Vojnosanitetski pregled, 2017)
Background/Aim. Cerebral palsy (CP) is one of the leading causes of neurological impairment in childhood. Preterm birth is a significant risk factor in the occurrence of CP. Clinical outcomes may include impairment of gross motor function and intellectual abilities, visual impairment and epilepsy. The aim of this study was to examine the relationships among gestational age, type of CP, functional ability and associated conditions. Methods. The sample size was 206 children with CP. The data were obtained from medical records and included gestational age at birth, clinical characteristics of CP and associated conditions. Clinical CP type was determined according to Surveillance of Cerebral Palsy in Europe (SCPE) and topographically. Gross motor function abilities were evaluated according to the Gross Motor Function Classification System (GMFCS). Results. More than half of the children with CP were born prematurely (54.4%). Statistically significant difference was noted with respect to the distribution of various clinical types of CP in relation to gestational age (p < 0.001). In the group with spastic bilateral CP type, there is a greater proportion of children born preterm. Statistically significant difference was noted in the functional classification based on GMFCS in terms of gestational age (p = 0.049), children born at earlier gestational age are classified at a higher GMFCS level of functional limitation. The greatest percentage of children (70.0%) affected by two or more associated conditions was found in the group that had extremely preterm birth, and that number declined with increasing maturity at birth. Epilepsy was more prevalent in children born at greater gestational age, and this difference in distribution was statistically significant (p = 0.032). Conclusion. The application of antenatal and postnatal protection of preterm children should be a significant component of the CP prevention strategy.